Calculating Masses of Pentaquarks Composed of Baryons and Mesons - M. Monemzadeh; N. Tazimi; Sh. Babaghodrat (Advances in High Energy Physics)
We consider an exotic baryon (pentaquark) as a bound state of two-body systems composed of a baryon (nucleon) and a meson. We used a baryon-meson picture to reduce a complicated five-body problem to simple two-body problems. The homogeneous Lippmann-Schwinger integral equation is solved in configuration space by using one-pion exchange potential. We calculate the masses of pentaquarks θc(uuddc¯) and θb(uuddb¯).